2022
DOI: 10.17583/ijelm.8847
|View full text |Cite
|
Sign up to set email alerts
|

Successful Pedagogical Leadership: Bibliometric Analysis from the Web of Science database (2017-2021)

Abstract: The concept of pedagogical leadership (PL) is vague and still developing in the field of Educational Leadership. This article examines the body of knowledge on this elusive term, to extract the key components that constitute the studies of PL in the last five years (2017-2020). The keyword of pedagogical leader* was solely used to search in the Web of Science database, and subsequently narrowed down to 54 reviewed articles through listed criteria for bibliometric analysis. Apart from the global bibliometric de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The study found a lack of peer-reviewed publications on this topic, highlighting the need for more research on the effects of the pandemic on scientific research and teaching/education. Bibliometric analysis of pedagogical leadership in the Web of Science database from 2017 to 2021 [12]. The study aimed to identify the trend of pedagogical leadership in published articles and found that it is an emerging theme in WoS databases, mostly cited from Nordic and European countries.…”
Section: Introductionmentioning
confidence: 99%
“…The study found a lack of peer-reviewed publications on this topic, highlighting the need for more research on the effects of the pandemic on scientific research and teaching/education. Bibliometric analysis of pedagogical leadership in the Web of Science database from 2017 to 2021 [12]. The study aimed to identify the trend of pedagogical leadership in published articles and found that it is an emerging theme in WoS databases, mostly cited from Nordic and European countries.…”
Section: Introductionmentioning
confidence: 99%
“…Leadership style is very important in education (Houshyar et al, 2020) and greatly impacts the teaching and learning process in schools (Aldulaimi, 2018). Even indirectly, the second most significant educational leader influences student learning after classroom teaching (Cheah & Lim, 2022). There is strong evidence that certain leadership behaviours are more effective than others in promoting student learning (Bush, 2018).…”
Section: Introductionmentioning
confidence: 99%